Rare earth metal modified layered positive electrode material for sodium ion battery and preparation method thereof

By introducing rare earth metal elements into the O3-type layered oxide positive electrode material of sodium ion battery for double modification, and using spray drying-solid phase sintering process, the problems of existing materials' capacity attenuation and poor rate performance are solved, achieving high efficiency and low cost performance improvement.

CN118919689BActive Publication Date: 2025-03-18NORTH CHINA ELECTRIC POWER UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411018123.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-26
Publication Date
2025-03-18
Estimated Expiration
2044-07-26

AI Technical Summary

Technical Problem

The existing sodium ion battery O3-type layered oxide positive electrode materials have problems of severe capacity attenuation and poor rate performance. The existing modification methods have high production costs and energy consumption, and long cycle stability and high rate performance still need to be improved.

Method used

Rare earth metal elements (such as erbium, ytterbium, letetrade, letetrade) are introduced for modification, and the ReO6 hexahedral structure is formed by doping into the lattice and surface distribution, which improves the structural stability of the material and the sodium ion diffusion ability, and obtains secondary particles with rich pore structure and good spherical shape through spray-drying-solid phase sintering process.

Benefits of technology

It significantly improves the long cycle performance and rate performance of sodium ion batteries, reduces production costs and energy consumption, and has good commercialization potential.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118919689B_ABST
    Figure CN118919689B_ABST
Patent Text Reader

Abstract

The present invention provides a rare earth metal modified layered positive electrode material for sodium ion batteries and a preparation method thereof. The main structure of the rare earth metal modified layered positive electrode material for sodium ion batteries is an O3 phase, and the chemical formula is NaNi a Fe b Mn c Re d O 2 , 0.28≤a≤0.33, 0.28≤b≤0.33, 0.28≤c≤0.33, 0≤d≤0.05, Re represents a rare earth metal element; the layered positive electrode material includes spherical secondary particles, the secondary particles include a plurality of stacked flaky primary particles, part of the rare earth metal elements are distributed on the surface of the secondary particles in the form of rare earth metal oxides, and part of the rare earth metal elements are doped in the layered positive electrode material lattice in the form of rare earth metal ions. The positive electrode material provided by the present invention is modified based on rare earth metal elements, and has good sphericity and rich pore structure. The battery containing the positive electrode material exhibits excellent rate performance and good cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of new energy technology, and in particular relates to a rare earth metal-modified layered positive electrode material for a sodium ion battery and a preparation method thereof. Background Art

[0002] Lithium-ion batteries have the advantages of high energy density, long cycle life and no memory effect, and are widely used in consumer electronics, electric vehicles and energy storage. With the continuous growth of market demand for lithium-ion batteries, the shortage of lithium resources has become increasingly prominent, which makes the development of high-performance new secondary battery systems an urgent need. In this context, sodium-ion batteries are considered to be one of the technologies that are expected to complement lithium-ion batteries due to their significant cost advantages.

[0003] Among the numerous cathode materials for sodium-ion batteries, layered oxide cathode materials have attracted great attention from researchers due to their high theoretical capacity and simple and scalable synthesis process. O3 and P2 are the two most common structures in layered oxide cathodes for sodium-ion batteries. Among them, O3 layered oxides are sodium-rich structures, and the sodium-poor P2 phase usually exhibits higher theoretical capacity. However, this type of cathode material still has problems such as severe capacity decay and poor rate performance that need to be solved. Ion doping, surface coating and morphology optimization are considered to be effective modification methods. These modification methods have their own advantages and disadvantages. For example: (1) Doping with active / inactive metal cations or non-metal anions can change the local coordination environment of transition metal ions to inhibit irreversible phase transitions, maintain structural stability, or widen the interlayer spacing of the crystal structure to achieve rapid sodium ion transport. A small amount of doping elements can greatly change the properties of the material. Therefore, the difficulty of ion doping lies in the selection of doping elements and the control of doping amount. (2) The surface coating layer can serve as an effective protective layer for the positive electrode material, reducing the side reactions between the positive electrode material and the electrolyte to improve the material's cycle stability. However, surface coating usually cannot increase the material's capacity. (3) Reasonable design of material morphology is usually based on improving the sodium ion diffusion rate. For example, the design of the nanostructure can not only shorten the electron transmission distance to improve the electronic conductivity of the positive electrode material, but its larger specific surface area allows the electrolyte to fully infiltrate to promote the transmission of sodium ions. However, the nanostructure has a larger surface energy, which can easily lead to self-agglomeration between nanoparticles and is more likely to have serious side reactions with the electrolyte.

[0004] The cobalt-free O3-type layered oxide NaNi1 / 3Fe1 / 3Mn1 / 3O2 has a high theoretical capacity and low raw material cost, and is a type of sodium-ion battery positive electrode material with great commercial prospects. However, NaNi1 / 3Fe1 / 3Mn1 / 3O2 positive electrode materials generally exhibit poor rate performance and stability. The modification method of the NaNi1 / 3Fe1 / 3Mn1 / 3O2 positive electrode material disclosed in the prior art CN113937262A and CN112456567A is to coat a metal oxide layer on the surface of the material, but the defect is that the modification process requires the prepared positive electrode material to be dispersed in a volatile solvent and then evaporated, and an additional secondary heat treatment is required to obtain a uniformly distributed and tightly bonded coating layer, which has high production costs and energy consumption; and the long-cycle stability and high-rate performance of the obtained positive electrode material still need to be improved. In addition, the methods for preparing O3-type layered oxide NaNi1 / 3Fe1 / 3Mn1 / 3O2 in the prior art mainly include solid phase sintering, sol-gel, liquid phase coprecipitation, etc. The positive electrode materials prepared by the solid phase sintering and sol-gel methods both present irregular particle morphology, and the resulting non-spherical morphology usually exhibits large charge transfer impedance and ion diffusion impedance, and the battery containing the positive electrode material has poor rate performance. The secondary particles of the positive electrode material prepared by the coprecipitation method are relatively dense, and the ion transmission channels on the particle surface are limited, which is not conducive to improving the rate performance of the battery. Summary of the invention

[0005] In order to solve all or part of the above technical problems, the present invention provides the following technical solutions:

[0006] One of the purposes of the present invention is to provide a rare earth metal modified layered positive electrode material for sodium ion batteries, wherein the main structure of the rare earth metal modified layered positive electrode material for sodium ion batteries is an O3 phase, and its chemical formula is NaNi a Fe b Mn c Re d O2, 0.28≤a≤0.33, 0.28≤b≤0.33, 0.28≤c≤0.33, 0≤d<0.05, Re represents a rare earth metal element;

[0007] The layered positive electrode material includes spherical secondary particles, which include multiple stacked flaky primary particles. Some of the rare earth metal elements are distributed on the surface of the secondary particles in the form of rare earth metal oxides, and some of the rare earth metal elements are doped in the layered positive electrode material lattice in the form of rare earth metal ions.

[0008] The present invention is NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3Rare earth metal elements are introduced into the O2 positive electrode material. The rare earth metal elements doped into the lattice replace the sites of transition metal ions and coordinate with oxygen to form ReO6 hexahedron, which has the following advantages: due to the large bond energy of Re-O, the obtained layered positive electrode material has better structural stability, which can alleviate the structural collapse of the positive electrode material during the cycle process to a certain extent, thereby improving the long cycle performance of the sodium ion battery; rare earth metal ions have a larger ionic radius than transition metal ions, which can increase the sodium ion interlayer spacing, reduce the sodium ion diffusion resistance, and improve the transmission capacity of sodium ion diffusion, which is conducive to obtaining better rate performance; the unique 4f5d electronic structure of rare earth metal ions is conducive to improving the conductivity of the positive electrode material, thereby improving the rate performance of the sodium ion battery. In addition, part of the rare earth metal elements are distributed on the surface of the secondary particles in the form of rare earth metal oxides, which has the following advantages: rare earth metal oxides have excellent chemical stability and thermal stability, stabilize the positive electrode / electrolyte interface during the cycle, inhibit the dissolution of transition metal ions and the loss of lattice oxygen, and improve the long cycle performance of sodium ion batteries; rare earth metal oxides have mixed conductive properties, which can improve the ion and electron conductivity of positive electrode materials; rare earth metal oxides can reduce the residual alkali content on the surface of the particles, and regulate the surface element valence state, inhibit the Jan-Taylor effect of trivalent manganese, and improve the structural stability of the material. In addition, the secondary particles of the positive electrode material provided by the present invention have good sphericity, and a rich pore structure is formed during the accumulation of the primary particles, which is not only conducive to the full penetration of the electrolyte and the increase of reaction sites, but also can buffer the structural stress changes of the positive electrode material during the charge and discharge process, thereby improving the electrochemical properties such as the rate performance and cycle stability of the layered oxide positive electrode material of the sodium ion battery.

[0009] In some embodiments, the particle size of the flaky primary particles is 100-300 nm, and the particle size of the spherical secondary particles is 10-35 μm.

[0010] In some embodiments, the layered positive electrode material has a rich pore structure with a porosity of 1-10%. The pores contained in the positive electrode material include mesopores and macropores. The size of the mesopores is 2-10 nm, and the size of the macropores is 60-100 nm.

[0011] In some embodiments, the doping concentration of the rare earth metal ions is 0-5 at%, and the content of the rare earth metal oxide is 0-5 wt%. When introduced in appropriate amounts, rare earth metal elements are not only beneficial to expanding the sodium ion transmission channel, but also can improve the material surface, and can maximize the dual optimization effect; however, since rare earth metal elements are inert elements, excessive introduction will lead to a decrease in the electrochemical performance of the positive electrode material.

[0012] In some embodiments, the main structure of the layered cathode material has a space group of R-3m, and the lattice constants a and c satisfy the following values: , the lattice volume V satisfies

[0013] In some embodiments, the rare earth metal element includes one or a combination of erbium, ytterbium or lutetium.

[0014] The second object of the present invention is to provide a method for preparing a rare earth metal-modified layered positive electrode material for a sodium ion battery, comprising:

[0015] Providing a precursor suspension containing a sodium source, a nickel source, an iron source, a manganese source and a rare earth metal source, wherein the rare earth metal source comprises a rare earth metal oxide;

[0016] At least using a spray drying method to prepare the precursor suspension into a precursor powder;

[0017] The precursor powder is solid-phase sintered in an oxygen-containing atmosphere to obtain a rare earth metal-modified layered positive electrode material for a sodium ion battery.

[0018] The present invention finds that the use of rare earth metal oxides as rare earth metal sources can not only obtain positive electrode materials with bulk doping and surface dual modification, but also the addition of rare earth metal oxides combined with a spray drying-solid phase sintering process can obtain secondary particles with higher sphericity; this may be because during the high-temperature sintering process, the rare earth metal oxides can promote sintering densification to a certain extent, maintain the spherical morphology obtained in the previous step of spray drying, and thus play a role in regulating the morphology of the secondary particles to a certain extent.

[0019] In some embodiments, the oxygen-containing atmosphere is air.

[0020] In some embodiments, the amounts of the sodium source, nickel source, iron source, manganese source and rare earth metal source are such that the molar ratio of sodium, nickel, iron, manganese and rare earth metal elements is 1-1.05: 0.28-0.33: 0.28-0.33: 0.28-0.33: 0-0.05.

[0021] In some embodiments, the rare earth metal oxide includes one or a combination of lutetium oxide, ytterbium oxide, or erbium oxide.

[0022] In some embodiments, the sodium source includes one or more of sodium carbonate, sodium hydroxide, sodium acetate, sodium nitrate, sodium oxalate, sodium sulfate and sodium citrate, but is not limited thereto.

[0023] In some embodiments, the nickel source includes one or more of nickel carbonate, nickel hydroxide, nickel acetate, nickel nitrate, nickel oxalate, nickel sulfate and nickel oxide, but is not limited thereto.

[0024] In some embodiments, the iron source includes one or more of ferric acetate, ferric nitrate, ferrous sulfate, ferrous oxide, ferrous oxide, ferric oxide and ferrosoferric oxide, but is not limited thereto.

[0025] In some embodiments, the manganese source includes one or more of manganese carbonate, manganese acetate, manganese nitrate, manganese sulfate, manganese dioxide, manganese trioxide and manganese tetraoxide, but is not limited thereto.

[0026] In some preferred embodiments, the sodium source includes sodium acetate, the nickel source includes nickel acetate, the iron source includes iron acetate, and the manganese source includes manganese acetate. The present invention finds that the use of acetate raw material formula combined with spray drying-solid phase sintering process in this system has a certain effect on forming an appropriate amount of pore structure. For example, when the raw material is mainly oxide, the secondary particles obtained tend to be more hollow, which will cause the positive electrode material to show lower mechanical strength and aggravate the side reaction between the electrolyte and the positive electrode; when the raw material is mainly sulfate, the secondary particles obtained have a denser surface, resulting in limited ion transmission channels.

[0027] In some embodiments, the rare earth metal source may also include one or more combinations of lutetium sources, ytterbium sources or erbium sources other than the rare earth metal oxide. For example, the lutetium source includes lutetium acetate, lutetium nitrate, lutetium sulfate, etc., the ytterbium source includes ytterbium acetate, ytterbium nitrate, ytterbium sulfate, etc., and the erbium source includes erbium acetate, erbium nitrate, erbium sulfate, etc.

[0028] In some embodiments, the conditions of the spray drying method include: an inlet temperature of 130-220° C., an outlet temperature of 80-180° C., and a centrifugal speed of 11000-15000 rpm.

[0029] In some embodiments, the solid phase sintering includes a first stage and a second stage, the temperature of the first stage is 300-500°C, the holding time is 5-8h, and the temperature of the second stage is 800-1100°C, the holding time is 8-20h.

[0030] In some embodiments, the heating rate of the first stage is 1-5° C. / min, and the heating rate of the second stage is 5-10° C. / min.

[0031] The third object of the present invention is to provide a rare earth metal-modified layered positive electrode material for sodium ion batteries prepared according to any of the methods described above.

[0032] A fourth object of the present invention is to provide an application of the rare earth metal-modified layered positive electrode material for sodium ion batteries in the preparation of positive electrodes for sodium ion batteries or sodium ion batteries.

[0033] A fifth object of the present invention is to provide a positive electrode for a sodium ion battery, comprising a positive electrode current collector and a positive electrode active material layer, wherein the positive electrode active material layer comprises the layered positive electrode material modified by a rare earth metal for a sodium ion battery.

[0034] The sixth object of the present invention is to provide a sodium ion battery, comprising a positive electrode, a negative electrode, an electrolyte and a separator, wherein the positive electrode is the positive electrode for the sodium ion battery.

[0035] Compared with the prior art, the present invention has at least the following beneficial effects:

[0036] (1) The present invention uses rare earth metal elements erbium, ytterbium, and lutetium to modify the nickel-iron-manganese-based positive electrode material of the sodium ion battery. The prepared modified positive electrode crystal structure has a larger c-axis size and a smaller a-axis size, that is, it has a larger sodium interlayer spacing for sodium ions to escape and embed; in addition, the distribution characteristics of the rare earth metal elements in different forms in the bulk phase and on the surface can improve the structural stability and chemical stability of the modified positive electrode material, and the sodium ion battery based on the positive electrode material has excellent rate performance and good cycle stability;

[0037] (2) The present invention uses a soluble transition metal salt solution in combination with a spray drying-solid phase sintering process to obtain secondary particles with a rich pore structure. The decomposition temperature of the soluble metal salt component is lower than the sintering treatment temperature. During the sintering process, elements such as carbon, hydrogen, and sulfur are removed from the positive electrode material in the form of gas, leaving pores. By adjusting the parameters of the spray drying process, the primary particle size can be adjusted to the nanometer level and the secondary particle size to the micrometer level. The agglomeration process of the nanometer-level primary particles can form an appropriate amount of pores. This unique pore structure feature effectively improves the rate performance of the positive electrode material. Furthermore, in this system, the raw material formula including acetate is used to more easily form a positive electrode material with an appropriate amount of pore structure.

[0038] (3) The present invention adopts rare earth metal oxides in combination with a spray drying-solid phase sintering process to obtain secondary particles with good sphericity. The rare earth metal oxides can promote sintering densification, so that the spherical morphology obtained in the previous step of spray drying can be maintained, thereby playing a role in regulating the morphology of the secondary particles to a certain extent; during the spray drying process, the rare earth metal oxides as insoluble components in the precursor solution will be partially enriched on the surface of the droplets, thereby playing a role in optimizing the surface structure of the positive electrode material to a certain extent, effectively improving the long-cycle stability of the positive electrode material; and compared with existing solid phase sintering, sol-gel, co-precipitation and other methods, the method of the present invention has a simple synthesis process and is easy to expand, which is conducive to the large-scale production of positive electrode materials and has great commercial potential. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0040] Figure 1 XRD patterns of the layered oxide positive electrode materials for sodium ion batteries in Example 1, Example 2 and Comparative Example 1 of the present invention;

[0041] Figure 2 The charge and discharge curves of the battery sample in Example 2 of the present invention at different rates;

[0042] Figure 3a , Figure 3b The SEM images of the layered oxide positive electrode material for a sodium ion battery in Example 1 of the present invention at different magnifications;

[0043] Figure 4 This is a SEM image of the layered oxide positive electrode material for a sodium ion battery in Example 10 of the present invention;

[0044] Figure 5 This is a SEM image of the layered oxide positive electrode material for a sodium ion battery in Example 11 of the present invention;

[0045] Figure 6 This is a SEM image of the layered oxide positive electrode material for a sodium ion battery in Comparative Example 2 of the present invention;

[0046] Figure 7 This is a SEM image of the layered oxide positive electrode material for a sodium ion battery in Comparative Example 3 of the present invention;

[0047] Figure 8 This is a long cycle performance diagram of the battery sample in Example 1 of the present invention;

[0048] Figure 9a , 9b These are SEM images of the sodium ion battery layered oxide positive electrode material in Comparative Example 1 of the present invention at different magnifications. DETAILED DESCRIPTION

[0049] The technical solution of the present invention is described in detail below in conjunction with specific embodiments so that those skilled in the art can better understand and implement the technical solution of the present invention. The specific functional details disclosed herein should not be interpreted as limiting, but only as the basis for the claims and as a representative basis for teaching those skilled in the art to adopt the present invention in different ways in any appropriate detailed embodiment.

[0050] Unless otherwise specified, the raw materials and reagents used in the present invention are all commercially available.

[0051] Example 1

[0052] (1) sodium acetate, nickel acetate, manganese acetate, iron acetate and lutetium oxide were weighed according to the metal molar ratio of Na:Ni:Fe:Mn:Lu=1.05:(0.98 / 3):(0.98 / 3):(0.98 / 3):0.02, and then added into deionized water in sequence, stirred at room temperature, and prepared into a mixed metal salt suspension;

[0053] (2) pumping the uniformly mixed metal salt suspension into a spray dryer for spray drying to obtain a precursor powder, wherein the spray dryer is set at an inlet temperature of 160° C., an outlet temperature of 110° C., and a centrifugal speed of 13200 rpm;

[0054] (3) In an air atmosphere, the obtained precursor powder was heated to 450°C at a heating rate of 2°C / min and pre-calcined for 6 h. After the pre-calcination, it was cooled to room temperature and then ground. Then, the temperature was heated to 900°C at a heating rate of 5°C / min in an air atmosphere and calcined for 15 h. After the calcination, it was cooled to 130°C and immediately transferred into an argon atmosphere glove box for storage to obtain a lutetium-modified sodium ion battery layered positive electrode active material with a chemical formula of Na(Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ) 0.98 Lu 0.02 02.

[0055] The sodium ion battery layered positive electrode material obtained above is used as the positive electrode active material to prepare the positive electrode sheet, as follows:

[0056] Preparation of positive electrode sheets: The positive electrode active material, conductive agent and binder are stirred and mixed in N-methylpyrrolidone (NMP) solvent in a mass ratio of 8:1:1. After the slurry is magnetically stirred for 5 hours, the slurry is evenly coated on a carbon-coated aluminum foil with a coater and vacuum dried at 80°C for 12 hours. After the punched sheets are taken out, they are placed in a glove box for standby use to obtain a lutetium-modified sodium-ion battery layered positive electrode sheet.

[0057] Electrochemical performance test: The above positive electrode and the sodium metal negative electrode were assembled into a half-cell for electrochemical performance test. GF / D glass fiber separator was used as the battery separator. The electrolyte formula was 1mol / L sodium perchlorate (NaClO4) dissolved in ethylene carbonate (EC) and propylene carbonate (PC) with a volume ratio of 1:1, and 5.0% fluoroethylene carbonate (FEC) was added as an electrolyte additive. The constant current charge and discharge test voltage range was 2.0-4.0V, and the nominal capacity was set to 150mAh / g; the rate performance test conditions were: 0.2C / 1C / 2C / 5C / 8C / 10C were charged and discharged 5 times in sequence; the long cycle performance test conditions were: 0.1C charge and discharge 3 times and then charge and discharge test at 1C rate.

[0058] Example 2

[0059] (1) sodium acetate, nickel acetate, manganese acetate, iron acetate and lutetium oxide were weighed according to the metal molar ratio of Na:Ni:Fe:Mn:Lu=1.05:0.33:0.33:0.33:0.01, and then added into deionized water in sequence, stirred at room temperature, and prepared into a mixed metal salt suspension;

[0060] (2) pumping the uniformly mixed metal salt suspension into a spray dryer for spray drying to obtain a precursor powder, wherein the spray dryer is set at an inlet temperature of 160° C., an outlet temperature of 110° C., and a centrifugal speed of 13200 rpm;

[0061] (3) In an air atmosphere, the obtained precursor powder was heated to 450°C at a heating rate of 2°C / min and pre-calcined for 6 h. After the pre-calcination, it was cooled to room temperature and then ground. Then, the temperature was heated to 900°C at a heating rate of 5°C / min in an air atmosphere and calcined for 15 h. After the calcination, it was cooled to 130°C and immediately transferred into an argon atmosphere glove box for storage to obtain a lutetium-modified sodium ion battery layered cathode material with a chemical formula of Na(Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ) 0.99 Lu c.01 O2;

[0062] The battery assembly and performance test were carried out according to the same positive electrode sheet preparation method and electrochemical performance test conditions as in Example 1.

[0063] Example 3

[0064] (1) sodium acetate, nickel acetate, manganese acetate, iron acetate and ytterbium oxide were weighed according to the metal molar ratio of Na:Ni:Fe:Mn:Yb=1.05:0.33:0.33:0.33:0.01, and then added into deionized water in sequence, stirred at room temperature, to prepare a mixed metal salt solution;

[0065] (2) pumping the uniformly mixed metal salt solution into a spray dryer for spray drying to obtain a precursor powder, setting the inlet temperature to 160° C., the outlet temperature to 110° C., and the centrifugal speed to 13200 rpm;

[0066] (3) In an air atmosphere, the obtained precursor powder was heated to 450°C at a heating rate of 2°C / min and pre-calcined for 6 h, cooled to room temperature and then ground, and then heated to 900°C at a heating rate of 5°C / min in an air atmosphere and calcined for 15 h. After the calcination, it was cooled to 130°C and immediately transferred into an argon atmosphere glove box for storage to obtain an ytterbium-modified sodium ion battery layered cathode material, the chemical formula of which is abbreviated as Na(Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ) 0.99 Yb 0.01 O2;

[0067] The battery assembly and performance test were carried out according to the same positive electrode sheet preparation method and electrochemical performance test conditions as in Example 1.

[0068] Example 4

[0069] (1) sodium acetate, nickel acetate, manganese acetate, iron acetate and ytterbium oxide were weighed according to the metal molar ratio of Na:Ni:Fe:Mn:Yb=1.05:(0.98 / 3):(0.98 / 3):(0.98 / 3):0.02, and then added into deionized water in sequence, stirred at room temperature, to prepare a mixed metal salt solution;

[0070] (2) pumping the uniformly mixed metal salt solution into a spray dryer for spray drying to obtain a precursor powder, setting the inlet temperature to 160° C., the outlet temperature to 110° C., and the centrifugal speed to 13200 rpm;

[0071] (3) In an air atmosphere, the obtained precursor powder was heated to 450°C at a heating rate of 2°C / min and pre-calcined for 6 h, cooled to room temperature and then ground, and then heated to 900°C at a heating rate of 5°C / min in an air atmosphere and calcined for 15 h. After the calcination, it was cooled to 130°C and immediately transferred into an argon atmosphere glove box for storage to obtain an ytterbium-modified sodium ion battery layered cathode material, the chemical formula of which is abbreviated as Na(Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ) 0.98 Yb 0.02 02;

[0072] The battery assembly and performance test were carried out according to the same positive electrode sheet preparation method and electrochemical performance test conditions as in Example 1.

[0073] Example 5

[0074] (1) sodium acetate, nickel acetate, manganese acetate, iron acetate and erbium oxide were weighed according to the metal molar ratio of Na:Ni:Fe:Mn:Er=1.05:0.33:0.33:0.33:0.01, and then added into deionized water in sequence, stirred at room temperature, to prepare a mixed metal salt solution;

[0075] (2) pumping the uniformly mixed metal salt solution into a spray dryer for spray drying to obtain a precursor powder, setting the inlet temperature to 160° C., the outlet temperature to 110° C., and the centrifugal speed to 13200 rpm;

[0076] (3) In an air atmosphere, the obtained precursor powder was heated to 450°C at a heating rate of 2°C / min and pre-calcined for 6 h, cooled to room temperature and then ground, and then heated to 900°C at a heating rate of 5°C / min in an air atmosphere and calcined for 15 h. After the calcination, it was cooled to 130°C and immediately transferred into an argon atmosphere glove box for storage to obtain an erbium-modified sodium ion battery layered positive electrode material with a chemical formula of Na(Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ) 0.99 Er 0.01 O2;

[0077] The battery assembly and performance test were carried out according to the same positive electrode sheet preparation method and electrochemical performance test conditions as in Example 1.

[0078] Example 6

[0079] (1) Sodium acetate, nickel acetate, manganese acetate, iron acetate and erbium oxide were weighed according to the metal molar ratio of Na:Ni:Fe:Mn:Er=1.05:(0.98 / 3):(0.98 / 3):(0.98 / 3):0.02, and then added into deionized water in sequence, stirred at room temperature, to prepare a mixed metal salt solution;

[0080] (2) pumping the uniformly mixed metal salt solution into a spray dryer for spray drying to obtain a precursor powder, setting the inlet temperature to 160° C., the outlet temperature to 110° C., and the centrifugal speed to 13200 rpm;

[0081] (3) In an air atmosphere, the obtained precursor powder was heated to 450°C at a heating rate of 2°C / min and pre-calcined for 6 h, cooled to room temperature and then ground, and then heated to 900°C at a heating rate of 5°C / min in an air atmosphere and calcined for 15 h. After the calcination, it was cooled to 130°C and immediately transferred into an argon atmosphere glove box for storage to obtain an erbium-modified sodium ion battery layered positive electrode material with a chemical formula of Na(Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ) 0.98 Er 0.02 02;

[0082] The battery assembly and performance test were carried out according to the same positive electrode sheet preparation method and electrochemical performance test conditions as in Example 1.

[0083] Example 7

[0084] The difference between Example 7 and Example 1 is that sodium acetate, nickel acetate, manganese acetate, iron acetate and lutetium oxide are weighed according to the metal molar ratio of Na:Ni:Fe:Mn:Lu=1.05:(0.97 / 3):(0.97 / 3):(0.97 / 3):0.03, and the rest is the same as Example 1. The chemical formula of the layered positive electrode material for the sodium ion battery obtained is Na(Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ) 0.97 Lu 0.03 O2.

[0085] Example 8

[0086] The difference between Example 8 and Example 1 is that sodium acetate, nickel acetate, manganese acetate, iron acetate and lutetium oxide are weighed according to the metal molar ratio of Na:Ni:Fe:Mn:Lu=1.05:(0.96 / 3):(0.96 / 3):(0.96 / 3):0.04, and the rest is the same as Example 1. The chemical formula of the layered positive electrode material for the sodium ion battery obtained is Na(Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ) 0.96 Lu 0.04 O2.

[0087] Example 9

[0088] The difference between Example 9 and Example 1 is that sodium acetate, nickel acetate, manganese acetate, iron acetate and lutetium oxide are weighed according to the metal molar ratio of Na:Ni:Fe:Mn:Lu=1.05:(0.95 / 3):(0.95 / 3):0.05, and the rest is the same as Example 1. The chemical formula of the layered positive electrode material for the sodium ion battery obtained is Na(Ni1 / 3 Fe 1 / 3 Mn 1 / 3 ) 0.95 Lu 0.05 O2.

[0089] Example 10

[0090] The only difference between Example 10 and Example 1 is that in step (1), the sodium source is sodium carbonate, the nickel source is nickel oxide, the iron source is ferric oxide, and the manganese source is manganese dioxide. The rest is implemented in the same way as Example 1 to obtain a sodium ion battery positive electrode material.

[0091] The battery assembly and performance test were carried out according to the same positive electrode sheet preparation method and electrochemical performance test conditions as in Example 1.

[0092] Embodiment 11

[0093] The only difference between Example 11 and Example 1 is that in step (1), the sodium source is sodium sulfate, the nickel source is nickel sulfate, the iron source is ferrous sulfate, and the manganese source is manganese sulfate. The rest is implemented in the same way as Example 1 to obtain a sodium ion battery positive electrode material.

[0094] The battery assembly and performance test were carried out according to the same positive electrode sheet preparation method and electrochemical performance test conditions as in Example 1.

[0095] Comparative Example 1

[0096] The only difference between Comparative Example 1 and Example 1 is that lutetium oxide is not added in step (1), and the other steps are carried out in the same manner as in Example 1 to obtain a positive electrode material for a sodium ion battery. The battery is assembled and the performance tested according to the same positive electrode sheet preparation method and electrochemical performance test conditions as in Example 1.

[0097] Comparative Example 2

[0098] The difference between Comparative Example 2 and Example 1 is that the spray drying method is replaced by a solvent thermal method to prepare the positive electrode material, which is as follows:

[0099] Sodium acetate, nickel acetate, manganese acetate, ferric acetate and lutetium oxide were weighed according to the metal molar ratio of Na:Ni:Fe:Mn:Lu=1.05:(0.98 / 3):(0.98 / 3):(0.98 / 3):0.02, dispersed in anhydrous ethanol to obtain a metal salt solution, evaporated it at an evaporation temperature of 105°C and then ground to obtain a precursor powder.

[0100] Then, the sodium ion battery positive electrode material was sintered according to the same solid phase sintering method as in Example 1, and the battery was assembled and the performance tested according to the same positive electrode sheet preparation method and electrochemical performance test conditions as in Example 1.

[0101] Comparative Example 3

[0102] The difference between Comparative Example 3 and Example 1 is that spray drying is replaced by dry ball milling followed by solid phase sintering, as follows:

[0103] Sodium carbonate, nickel oxide, manganese dioxide, ferric oxide and lutetium oxide were weighed and uniformly mixed according to the metal molar ratio of Na:Ni:Fe:Mn:Lu=1.05:(0.98 / 3):(0.98 / 3):(0.98 / 3):0.02 to obtain a mixture, and the mixture was dry-milled at a ball mill speed of 240 rpm for 12 h to obtain a precursor powder;

[0104] Then, the sodium ion battery positive electrode material was sintered according to the same solid phase sintering method as in Example 1, and the battery was assembled and the performance tested according to the same positive electrode sheet preparation method and electrochemical performance test conditions as in Example 1.

[0105] Comparative Example 4

[0106] The difference between Comparative Example 4 and Example 1 is that the lutetium oxide in Example 1 is replaced by lutetium acetate, and the rest is implemented in the same manner as Example 1.

[0107] Comparative Example 5

[0108] The difference between Comparative Example 5 and Example 4 is that the ytterbium oxide in Example 4 is replaced by ytterbium acetate, and the rest is the same as Example 4.

[0109] Comparative Example 6

[0110] The difference between Comparative Example 6 and Example 6 is that the erbium oxide in Example 6 is replaced by erbium acetate, and the rest is the same as Example 6.

[0111] Comparative Example 7

[0112] The difference between Comparative Example 7 and Example 1 is that lutetium oxide is replaced by cerium oxide, and the rest is the same as Example 1.

[0113] Comparative Example 8

[0114] The difference between Comparative Example 8 and Example 1 is that lutetium oxide is replaced by lanthanum oxide, and the rest is the same as Example 1.

[0115] Phase analysis was performed on the positive electrode materials prepared in Example 1, Example 2 and Comparative Example 1. Figure 1From the XRD spectra corresponding to Example 1 and Example 2, it can be seen that with the increase of the content of rare earth metal element lutetium (Lu), the (003) diffraction peak gradually shifts to a smaller angle, and the second phase content of lutetium trioxide (Lu2O3) increases, proving that Lu is partially doped into the bulk lattice of the material, and the remaining lutetium still exists on the surface of the material in the form of lutetium trioxide.

[0116] The layered oxide positive electrode material prepared in Example 1 was tested for battery rate performance. Figure 2 These are the charge and discharge curves of the battery sample of Example 1 at different rates. The discharge specific capacities of the batteries at rates of 0.2C, 1C, 2C, 5C, 8C and 10C are 147 mAh / g, 141 mAh / g, 138 mAh / g, 130 mAh / g, 123 mAh / g and 119 mAh / g, respectively.

[0117] Figure 3a , 3b These are SEM images of the sodium ion battery layered oxide positive electrode material in Example 2 at different magnifications, which show that the positive electrode material obtained by the preparation method of the present invention is a secondary particle formed by the agglomeration of many small primary particles, there is a small amount of residual alkali on the surface of the particles, and the secondary particles have good sphericity. Figure 9a , Figure 9b The SEM images of the positive electrode material of Comparative Example 1 at different magnifications show that the material is composed of secondary particles formed by the aggregation of many small primary particles. The particle surface is relatively rough, and there is a large amount of residual alkali. The sphericity of the secondary particles is low. Figure 3a , Figure 9a It can be seen that without adding lutetium oxide, although the spray drying and solid phase sintering processes used in Comparative Example 1 are the same, the sphericity of the secondary particles obtained is lower, indicating that rare earth metal oxides play a certain role in regulating the spherical morphology of the secondary particles.

[0118] Comparative Example 2 and Comparative Example 3 respectively verify the morphology and performance of the positive electrode materials obtained by replacing the spray drying method with the solvent thermal method and the dry ball milling combined with the solid phase sintering. Figure 6 and Figure 7 As shown, it is found that in Comparative Examples 2 and 3, when lutetium oxide is added, the secondary particles obtained have low sphericity, indicating that the spray drying combined with solid phase sintering adopted in the present invention also has a certain effect on regulating the spherical morphology of the secondary particles.

[0119] Example 10 and Example 11 respectively verify the morphology and performance of the positive electrode material obtained by replacing the acetate raw material formula with the oxide raw material formula and the sulfate raw material formula and spray drying-solid phase sintering. Figure 4 and Figure 5As shown, it is found that the secondary particles obtained in Example 10 and Example 11 have a higher sphericity, but the secondary particles of Example 10 have a hollow structure, and the secondary particles of Example 11 have a denser surface, indicating that the acetate raw material formula combined with the spray drying-solid phase sintering process of the present invention also has a certain effect on the formation of an appropriate amount of pore structure, and the porosity and pore size obtained by using the acetate raw material are more appropriate. Furthermore, in combination with Comparative Example 1, Example 10, Example 11, Comparative Example 1, Comparative Example 2 and Comparative Example 3, it can be seen that the present invention uses rare earth metal oxides to not only achieve dual modification of the bulk and surface of the positive electrode material, but also uses acetate and rare earth metal oxides as the raw material formula, and cooperates with the spray drying-solid phase sintering process to obtain a spherical layered oxide positive electrode material with an appropriate amount of pore structure. Compared with the amorphous layered oxide positive electrode materials in the prior art, the spherical morphology can effectively alleviate the problem of residual alkali on the particle surface, and the appropriate amount of pore structure can reduce the diffusion distance of sodium ions and alleviate stress changes during the cycle, thereby improving the long-cycle stability and rate performance of the positive electrode material.

[0120] Figure 8 This is a cycle performance diagram of the battery sample of Example 1 of the present invention at a 1C rate. After 300 cycles, the discharge specific capacity of the battery is 115.7 mAh / g, and the capacity retention rate is 83.69%.

[0121] Table 1 summarizes the elemental composition, morphology, particle size and porosity characteristics of the positive electrode materials in the embodiments of the present invention and the comparative examples. Table 2 shows the relevant performance of the sodium ion batteries assembled based on the positive electrode materials in the embodiments of the present invention and the comparative examples.

[0122] Table 1 Composition and related properties of positive electrode materials in the embodiments of the present invention and comparative examples

[0123]

[0124]

[0125] Table 2 Related performances of sodium ion batteries obtained in the embodiments of the present invention and comparative examples

[0126]

[0127]

[0128] The various aspects, embodiments, features and examples of the present invention should be considered as illustrative in all aspects and are not intended to limit the present invention, the scope of the present invention is defined only by the claims. Other embodiments, modifications and uses will be apparent to those skilled in the art without departing from the spirit and scope of the claimed invention.

[0129] In addition, the inventors of this case also referred to the aforementioned embodiments and conducted experiments with other raw materials, process operations, and process conditions described in this specification, and obtained relatively ideal results.

[0130] Although the present invention has been described with reference to illustrative embodiments, it will be appreciated by those skilled in the art that various other changes, omissions and / or additions may be made without departing from the spirit and scope of the present invention and that the elements of the embodiments may be replaced by substantial equivalents. In addition, many modifications may be made without departing from the scope of the present invention to adapt specific circumstances or materials to the teachings of the present invention. Therefore, it is not intended herein to limit the present invention to the disclosed specific embodiments for performing the present invention, but it is intended that the present invention will include all embodiments within the scope of the appended claims. In addition, unless specifically stated, any use of the terms first, second, etc. does not indicate any order or importance, but rather uses the terms first, second, etc. to distinguish one element from another.

Claims

1. A rare earth metal-modified layered positive electrode material for sodium ion batteries, characterized in that: The main structure of the layered cathode material modified with rare earth metals for the sodium-ion battery is of the O3 phase, and the chemical formula is NaNi a Fe b Mn c Re d O2, where 0.28 ≤ a ≤ 0.33, 0.28 ≤ b ≤ 0.33, 0.28 ≤ c ≤ 0.33, 0 < d ≤ 0.05, Re represents a rare earth metal element and is selected from one or a combination of erbium, ytterbium or lutetium; the space group of the main structure of the layered cathode material satisfies: The lattice volume V satisfies The layered positive electrode material includes spherical secondary particles, the secondary particles include a plurality of stacked flaky primary particles, the particle size of the flaky primary particles is 100 to 300 nm, and the particle size of the spherical secondary particles is 10 to 35 μm; Part of the rare earth metal elements is distributed on the surface of the secondary particles in the form of rare earth metal oxides, and part of the rare earth metal elements is doped in the layered positive electrode material lattice in the form of rare earth metal ions, and replaces the sites of transition metal ions to coordinate with oxygen to form ReO6 hexahedrons; the doping concentration of the rare earth metal ions is greater than 0 and less than or equal to 5at%, and the content of the rare earth metal oxide is greater than 0 and less than or equal to 5wt%; Furthermore, the porosity of the layered positive electrode material is 1-10%, wherein the pores contained therein include mesopores and macropores, the size of the mesopores is 2-10 nm, and the size of the macropores is 60-100 nm.

2. The method for preparing the rare earth metal-modified layered positive electrode material for sodium ion battery according to claim 1, characterized in that: include: Providing a precursor suspension containing sodium acetate, nickel acetate, iron acetate, manganese acetate and a rare earth metal source, wherein the rare earth metal source comprises a rare earth metal oxide, and the rare earth metal oxide is selected from one or a combination of lutetium oxide, ytterbium oxide or erbium oxide; The precursor suspension is made into a precursor powder by a spray drying method, wherein the conditions of the spray drying method include: an inlet temperature of 130 to 220° C., an outlet temperature of 80 to 180° C., and a centrifugal speed of 11000 to 15000 rpm; In an oxygen-containing atmosphere, the precursor powder is solid-phase sintered, and the solid-phase sintering includes a first stage and a second stage. The temperature of the first stage is 300-500° C., and the insulation time is 5-8 hours. The temperature of the second stage is 800-1100° C., and the insulation time is 8-20 hours, to obtain a rare earth metal-modified layered positive electrode material for a sodium ion battery.

3. The preparation method according to claim 2, characterized in that: The amounts of sodium acetate, nickel acetate, iron acetate, manganese acetate and rare earth metal source are such that the molar ratio of sodium, nickel, iron, manganese and rare earth metal elements is 1-1.05:0.28-0.33:0.28-0.33:0.28-0.33:0-0.

05.

4. The preparation method according to claim 2, characterized in that: The heating rate of the first stage is 1-5°C / min, and the heating rate of the second stage is 5-10°C / min.

5. A rare earth metal-modified layered positive electrode material for sodium ion batteries prepared according to the method of any one of claims 2 to 4.

6. Use of the rare earth metal-modified layered positive electrode material for sodium ion batteries according to claim 1 or 5 in preparing positive electrodes for sodium ion batteries or sodium ion batteries.

7. A positive electrode for a sodium ion battery, comprising a positive electrode current collector and a positive electrode active material layer, characterized in that: The positive electrode active material layer comprises the layered positive electrode material modified with a rare earth metal for a sodium ion battery as claimed in claim 1 or 5.

8. A sodium ion battery comprising a positive electrode, a negative electrode, an electrolyte and a separator, characterized in that: The positive electrode is the positive electrode for a sodium ion battery according to claim 7.

Citation Information

Patent Citations

  • Preparation method of sodium ion battery positive electrode material with coating structure

    CN112456567A

  • Metal oxide modified positive electrode material for sodium ion battery and preparation method and application of metal oxide modified positive electrode material

    CN113937262A

  • Positive electrode material and preparation method thereof, positive electrode plate and O3 type layered sodium ion battery

    CN115207339A

  • Cerium-modified sodium ion battery layered positive electrode material and preparation method thereof

    CN116470022A

  • Inert metal ion doped nickel iron sodium manganate ternary positive electrode material and preparation method thereof

    CN116646514A